(untitled) - Milan Spears, Deanne (Boston, 2006)
Designed for reading courses at the intermediate and advanced level, Developing Critical Reading Skills uses practice prose similar to the kind that students will encounter in the classroom, encouraging them to analyze, interpret, question, and even challenge the words of the writer. The seventh edition continues to feature a wide range of interesting and diverse selections, excellent coverage of critical reading skills, and a concluding section on reading short stories. It now also includes coverage of reading textbooks and interpreting visuals
Keywords: Reading (Higher education),Reading comprehension,Kỹ năng đọc hiểu,Phát triển kỹ năng đọc